Effective connectivity of the anterior hippocampus predicts recollection confidence during natural memory retrieval - Yudan Ren; Vinh T. Nguyen; Saurabh Sonkusare; Jinglei Lv; Tianji Pang; Lei Guo; Simon B. Eickhoff; Michael Breakspear; Christine C. Guo (Nature Communications, 2018)
While memory is often studied using voluntary recollection, the neural correlates of involuntary memory recall and its effect on cognition are unclear. Here, Ren and colleagues show that the effective connectivity from the anterior hippocampus to the precuneus can predict the strength of involuntary retrieval of episodic memory.